Effect of Video-Based Health Education on Adolescents Knowledge of Risky Sexual Behavior and STDs - Irma Hermawati; Ima Sukmawati; Sri Utami Asmarani; Yuyun Rahayu; Heni Marliany; Lusi Lestari; Neli Sunarni (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2026)
Introduction: Adolescents are a vulnerable group to risky sexual behavior due to biological, psychological, and social changes that occur during the transition to adulthood. Limited knowledge about the dangers of risky sexual behavior and sexually transmitted diseases (STDs) can increase the risk of reproductive health problems, sexually transmitted infections, and unintended pregnancies. Therefore, appropriate educational strategies are needed to improve adolescents knowledge regarding reproductive health. One effective approach is the use of video-based health education, which can present information in an engaging and easily understandable format. Objective: This study aimed to determine the effect of video-based health education on adolescents knowledge about the dangers of risky sexual behavior and sexually transmitted diseases. Method: This study employed a quantitative method with a pre-experimental design using a one-group pre-test and post-test approach. The research was conducted among students of SMKN 1 Kawali in 2025. The sample consisted of students who met the inclusion criteria and were selected using a total sampling technique. Data were collected using a structured questionnaire to measure adolescents knowledge before and after the intervention. The data were analyzed using the Wilcoxon test. Results: The results showed an increase in adolescents knowledge after receiving video-based health education. Statistical analysis using the Wilcoxon test indicated a significant difference between pre-test and post-test scores, with a p-value < 0.05. Conclusion: Video-based health education has a significant effect on improving adolescents knowledge about the dangers of risky sexual behavior and sexually transmitted diseases. Therefore, the use of video as an educational medium can be considered an effective strategy in health promotion programs for adolescents.